Ghost world [videorecording (DVD)] - Zwigoff, Terry; Birch, Thora; Johansson, Scarlett, 1984-; Renfro, Brad, 1982-2008; Balaban, Bob; Douglas, Illeana, 1965-; Buscemi, Steve, 1957-; Clowes, Daniel (United Artists ; Distributed by MGM Home Entertainment, 2001)
"While their classmates head for college, Enid and Rebecca focus their energies on tormenting those around them! From a goofy convenience store clerk to an eccentric art teacher, these two saboteurs wreak havoc on all who cross their paths. But when they zero in on an oddball loner looking for Miss Right, their seemingly innocent meddling threatens to shatter one of their hearts ... and their lifelong friendship!"--Container.